Pengalaman Ibu dengan Bayi Berat Lahir Rendah yang Dirawat di Rumah Sakit - Kurniawan Dewi Budiarti; Sri Yekti Widadi; Gina Fitri Herdianti (STIKes Karsa Husada Garut, 2017)
The experience of mothers who have low birth weight infants is different from the experiences of mothers with infants in general. Mothers of low birth weight infants faced with a number of psychological tasks that may interfere with the relationship between mother and baby. This research aims to know how the mothers experiences with low birth weight infants were being treated in the hospital. There are 6 participants were taken with a purposive sampling. The result of this research identified five themes, that is : (1) Mother’s Perception of Low Birth Weight Infants, (2) Mother’s Response of Low Birth Weight Infants, (3) Causes of Stress at The Time of The Mother Has a Low Birth Weight Infants, (4) Mother Expectations of Caring a Low Birth Weight Infants in the hospital, and (5) Source of Support Obtained Mother. Conclusions support are needed, the support of family or health workers